ATTITUDE OF HISTORICAL AND LITERARY CHARACTERS OF ALISHER NAVOI TO ART - Hayitov Shavkat Ahmadovich; Maftuna Bafoeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article deals with A. Navoi’s and his literary characters’ attitude to art and the people who work in the field of art.